DETERMINAN FAKTOR NILAI PERUSAHAAN - Rismawandi Rismawandi (MANAJEMEN, 2025)
The industrial sector that plays an important role in improving the economy and sustainable development in the world is the mining sector. Despite its significant contribution, this industry faces challenges in managing various negative impacts that can pollute the environment and society. Conflicts can arise with the surrounding community due to differences in views or perceptions about existing natural resources. Investors assess a company's success based on the value it holds. This study aims to analyze the impact of stock prices, profitability, and debt covenant on company value, as measured using Price Book Value, in mining companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The data analysis method used is multiple linear regression. The results of the study indicate that stock prices, profitability, and debt covenant have a positive and significant effect on company value.